PROSPECTS OF THE PRIVATE LOCOMOTIVES USAGE FOR GOODS TRAFFIC IN THE DIRECTION OF SEA PORTS - Kozachenko, D. M.; Ochkasov, O. B.; Shepotenko, A. P.; Sannytsky, N. M. (Science and Transport Progress, 2017)
Purpose. At the present time, Ukraine's mainline railway transport is entirely in state ownership. Ukraine has undertaken to implement the European Union Directives providing of non-discriminatory access to the railway infrastructure of independent carriers. A considerable quantity of options significantly affects the working conditions of carriers that do not depend on Ukrzaliznytsia. One of the tasks that arises when performing transportation by independent carriers is the organization of private locomotives operation and their servicing by engine crews. The purpose of the article is to evaluate the technical characteristic of the private locomotives usage in order to perform goods traffic in the direction of sea ports. Methodology. The researches were carried out on the basis of methods for organizing the operational work of railways and methods of traction calculations. Findings. The paper highlights the problem of goods traffic organization to seaports by independent carriers. It determines the requirements for equipment for diesel locomotives and electric locomotives depending on the distance of transportation. Permissible distances that can be served by engine crews in performing the requirements for the duration of their continuous operation were also determined. Schemes of infrastructure objects location for the locomotives and engine crews operation have been developed. It was established that diesel locomotives of independent carriers will be able to serve transportation between loading and unloading stations up to 822 km, and electric locomotives up to 1000 km with the construction of the main part of the locomotive infrastructure at the port station. The performed calculations show the potential coverage of rail transportation to sea ports by independent carriers with the use of its own locomotive infrastructure. To define more exactly the haul length of train servicing by locomotives and locomotives by engine crews, it is necessary to perform additional calculations based on detailed service section profiles. Originality. Access circuitry of locomotives and engine crews of independent carriers when servicing sea ports by them were obtained. Practical value. The results of the research allow evaluating the needs in the locomotive infrastructure that arise at opening of the rail market for independent carriers.